The antibacterial effects of Melaleuca alternifolia, Pelargonium graveolens and Cymbopogon martinii essential oils and major compounds on liquid and vapor phase - Andrade, Bruna Fernanda Murbach Teles [UNESP] (2016)
Essential oils (EOs) are natural products from plant secondary metabolism. The antibacterial activity of EOs from Melaleuca alternifolia, Pelargonium graveolens and Cymbopogon martinii and terpinen-4-ol, citronellol and geraniol were investigated both in their liquid and vapor phases against Gram-positive and Gram-negative strains. From microdilution tests, geraniol showed a minimal inhibitory concentration (MIC) value of 0.05% v/v against almost all strains. According to the inverted plate assays, Klebsiella pneumoniae was highly sensitive (inhibitory zone of 31 mm) to terpinen-4-ol and 100% of reduction under vapor microenvironment assays were recorded. The effectiveness of compounds as antibacterial agents was demonstrated, highlighting the damage caused to strains by C. martinii EO and geraniol vapors through transmission electron microscopy, and it was observed that geraniol was probably responsible for the antibacterial effect of C. martinii EO.